CONTRASTIVE ANALYSIS OF PHRASEOLOGICAL UNITS WITH THE COMPONENT EAR IN ENGLISH AND UZBEK LANGUAGES (Web of Teachers: Inderscience Research, 2025)
Phraseological units are an essential part of any language, reflecting the culture, traditions, and worldviews of the speakers. This study explores the phraseological units containing the component ear in English and Uzbek, analyzing their similarities, differences, and cultural implications.